Effects of Panaxadiol Saponins Component as A New Chinese Patent Medicine on Proliferation, Differentiation and Corresponding Gene Expression Profile of Megakaryocytes - 温伟为 孙馨 庄海峰 林筱洁 郑智茵 高瑞兰 尹利明 (Chinese journal of integrative medicine, 2016)
Objective： To investigate the effects of panaxadiol saponins component （PDS-C） isolated from total saponins of panax ginseng on proliferation, differentiation and corresponding gone expression profile of megakaryocytes. Methods： Bone marrow culture of colony forming assay of megakaryocytic progenitor cells （CFU-MK） was observed for the promoting proliferation mediated by PDS-C, and differentiation of megakaryocytic blasts caused by PDS-C was analyzed with flow cytometry in CHRF-288 and Meg-01 cells, as well as proliferation, differentiation-related genes expression profile and protein expression levels were detected by human gone expression microarray and western blot. Results： In response to PDS-C 10, 20 and 50 mg/L, CFU-MK from 10 human bone marrow samples was increased by 28.9± 2.7%, 41.0% ± 3.2% and 40.5% ± 2.6% over untreated control, respectively （P〈0.01, each）. Flow cytometry analysis showed that PDS-C treated CHRF-288 cells and Meg-01 cells significantly increased in CD42b, CD41, TSP and CD36 positive ratio, respectively. PDS-C induced 29 genes up-regulated more than two-fold commonly in both cells detected by human expression microarray representing 4000 known genes. The protein expression levels of ZNF91, c-Fos, BTF3a, GATA-1, RGS2, NDRG2 and RUNX1 were increased with western blot in correspond to microarray results. Conclusion： PDS-C as an effective component for hematopoiesis, play the role to enhance proliferation and differentiation of megakaryocytes, also up-regulated expression of proliferation, differentiation-related genes and proteins in vitro. KEYWORDS panaxadiol saponins, megakaryocyte, gone expression profile, proliferation, differentiation